Goniothalamin induces cell cycle arrest and apoptosis in H400 human oral squamous cell carcinoma: A caspase-dependent mitochondrial-mediated pathway with downregulation of NF-κβ - Abd Manaf, Ali; Fahme A., Kaid; Rola, Ali (Elsevier Ltd, 2016)
Goniothalamin is a natural occurring styryl-lactone compound isolated from Goniothalamus macrophyllus. It had been demonstrated to process promising anticancer activity on various cancer cell lines. However, little study has been carried out on oral cancer. The aim of this study was to determine the cytotoxic effects of goniothalamin against H400 oral cancer cells and its underlying molecular pathways. Results from MTT assay demonstrated that goniothalamin exhibited selective cytotoxicity as well as inhibited cells growth of H400 in dose and time-dependent manner. This was achieved primarily via apoptosis where apoptotic bodies and membrane blebbing were observed using AO/PI and DAPI/Annexin V-FITC fluorescence double staining. In order to understand the apoptosis mechanisms induced by goniothalamin, apoptosis assessment based on mitochondrial membrane potential assay and cytochrome c enzyme-linked immunosorbent assay were carried out. Results demonstrated that the depolarization of mitochondrial transmembrane potential facilitated the release of mitochondrial cytochrome c into cytosol. Caspases assays revealed the activation of initiator caspase-9 and executioner caspase-3/7 in dose-dependent manners. This form of apoptosis was closely associated with the regulation on Bcl-2 family proteins, cell cycle arrest at S phase and inhibition of NF-κβ translocation from cytoplasm to nucleus. Conclusion, goniothalamin has the potential to act as an anticancer agent against human oral squamous cell carcinoma (H400 cells).